An efficient 2D 11B-11B solid-state NMR spectroscopy strategy for monitoring covalent self-assembly of boronic acid-derived compounds: the transformation and unique architecture of bortezomib molecules in the solid state - Brus, J; Czernek, J; Urbanova, M; Kobera, L; Jegorov, A (Physical chemistry chemical physics, 2016)
The difficulty in the prediction of the complicated solid-state structure of boronic acid derivatives, resulting from the complex pathway of reversible covalent interactions, represents a significant obstacle to the development of a new generation of advanced supramolecular systems such as covalent organic frameworks of efficient anticancer drugs. In this contribution, various 2D 11B-11B solid-state NMR correlation techniques supported by DFT calculations were explored to formulate a reliable tool for monitoring the covalent assembly of boronic acid residues in the solid state. This way, the self-condensation of bortezomib molecules was investigated, different local constitutions of boroxine motifs were unveiled, and the previously unreported boroxine structures of bortezomib polymorphs exhibiting secondary coordination were discovered and described in detail. The recorded 11B NMR parameters responded sensitively to subtle changes in the local geometries, which were reliably interpreted and directly visualized by the DFT calculations. A uniform 2.6 Å distance in bortezomib 11B-11B spin pairs was conclusively identified by the through-space 11B-11B double-quantum (DQ) coherence build-up curves, whereas distinct 2D 11B-11B DQ correlation patterns revealed unique boroxine structures existing in the crystalline as well as amorphous state. The boroxine rings were found to be internally stabilized through the transformation of the trigonal boron sites toward tetrahedral geometry, as the secondary five-membered rings were formed. This way, the nature of bortezomib polymorphism is disclosed, and an efficient strategy for exploring the assembly of boronic acid derivatives in the solid state, for which no crystallographic data are available, is thus demonstrated.